Geotechnical Frontiers 2017. selected papers from sessions of Geotechnical Frontiers 2017, March 12-15, 2017, Orlando, Florida - Brandon, Thomas L.; Valentine, Richard J. (GSP (Series) ;, 2017)
Contains 97 peer-reviewed papers on geomaterials, modeling and testing. Topics include: application of geofibers, behavior of compacted clays, energy geostructures, geosynthetics research, modeling and testing, laboratory testing of offshore sediments, coastal geotechnics, soil and rock testing and modeling, thermal and hydraulic conduction, and unconventional geoengineering materials.